In silico determination and analysis of sea cucumber (Holothuroidea) allergenicity and cross-reactivity - Reynosa, Clarissa Antoinette T.; Anapi, Gerieka R. (Quezon City University of the Philippines Diliman, 2024)
Global consumption of seafood has been steadily increasing affecting 1-3% of the population, with the demand for sea cucumbers (Holothuroidea) on the rise due to its high bioactive compound and metabolite content. However, the study of allergenicity and cross-reactivity of sea cucumbers remain insufficiently investigated despite its high demand as bêche-de-mer in the global trepang trade due to its antitumor, anticoagulant, antimicrobial, and antioxidant properties. In this study, the allergenicity and cross-reactivity of sandfish (Holothuria scabra), dragonfish (Stichopus horrens), and prickly redfish (Thelenota ananas) are evaluated. Common potential allergens in three species of Holothuroidea are cytochrome b, cytochrome c oxidase subunits 1 and 3, and NADH-ubiquinone oxidoreductase chain 5. For S. horrens and T. ananas, NADH-ubiquinone oxidoreductase chain 2 was also detected as potentially allergenic proteins together with NADH-ubiquinone oxidoreductase chain 4 in S. horrens. These potential allergens were then found to be cross-reactive to allergens in several food sources (e.g., yellowfin tuna, atlantic cod, soybean, peanut). Peptide sequences of the B-cell epitopes were predicted which determined that the amino acids involved possess surface accessibility, hydrophilicity, and antigenicity – essential properties of B-cell epitopes. The T-cell epitopes of the allergenic protein also possess binding affinity to the class II HLA associated with wheat, peanut, lichwort, olive, rye, castor bean, apple, and orange allergies. The tertiary structures of the potential allergens were modeled for a proper visualization which obtained high GMQE and ERRAT scores, indicating good quality of 3D models produced. However, the Verify3D scores were found to be below 80%, signifying the need for further compatibility of the 3D structure to its 1D amino acid sequence.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Allergens; Food allergy; Sea cucumbers; Allergenicity; Cross-reactivity.; Holothuroidea